Representações sociais de estudantes de uma universidade pública baiana sobre a criatividade - Lima, Daniela Cristina Ribeiro de (2019)
Creativity is a sociocultural phenomenon, multidimensional and not only dependent on intrapsychic characteristics. Based on this premise, this research aimed to analyze, from the perspective of the students of the Degree in Pedagogy of a public university of Bahia, the social representations of creativity. As for the specific objectives, they aimed to: identify the internal structure of the social representation of creativity of Pedagogy students; verify the stability of the elements that are most likely to be part of the central core of the creativity representation; and identify the characteristics of the teachers considered in the exercise of their profession built by students in dialogic in interactions in the focus group. The literature review addressed four topics: concepts of creativity and some theoretical approaches; creativity in higher education; and the characteristics of the creative teacher; and the Theory of Social Representations. The methodology was quanti-qualitative, being realized through three instruments: the technique of free association of words, from the term inducer "creativity"; focal group; and the method of successive hierarchical trials. The first of these instruments, applied to 104 participants, resulted in 234 evocations; the others were applied to twelve participants. The data collected through the free association of words were initially analyzed by means of frequencies and percentages and, later, they were delineated from qualitative analytical categories, based on the following dimensions: cognitive, emotion, esthetics and genesis. With respect to the data analysis obtained in the trials, these were done through statistical operations. As for the material produced in the focal group, they were submitted to content analysis. The qualitative data analysis software ATLAS.ti, version 8.4 was used to encode and categorize the characteristics of the creative teacher in terms of thematic content. Descriptive statistics were used to characterize the participants. One of the results was that students define creativity more in terms of individual aspects related to the cognitive dimension: ideas and imagination, than of contextual factors, distancing themselves from the current theoretical perspectives that present a more systemic view of this phenomenon that includes the individual and the context. In addition, it highlights the elements that can constitute the central dimension of the representation of creativity, namely: ideas and imagination. As for the characteristics of the creative teacher, the responses of the informants were grouped into three distinct categories: teacher attributes (sensitivity, flexibility, dynamic, reflective, content mastery, observer, curious, coherence, researcher), relationship characteristics (providing freedom and respect for students, welcoming, dialogic, friendly relationship) and teaching strategies (novelty). The findings also raise reflections on what students think and expect from their higher education teachers. It also points to the need to promote creativity in teacher education. It is hoped that this research will contribute to the advancement of knowledge about the phenomenon of creativity, awaken and increase the awareness of its importance and its value in Higher Education, especially in teacher training courses.